WACANA-WACANA FILOSOFIS BALI DALAM PERTUNJUKAN ARJA RRI DENPASAR LAKON PAYUK PRUNGPUNG - Suarta, Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
Dramatari Arja is one form of classical dramatari is still favored by the Balinese. One element of the discourse package charm is unique and diverse. The diversity of discourse which appears in the show plays Payuk Prungprung Arja RRI Denpasar received a positive reception from the people of Balinese. With the diversity of semiotics theory of discourse that will be revealed the meanings contained therein. In general meaning which can be expressed in this research includes religious meaning, the meaning of magic, the meaning of ruabhineda, the meaning of trihita karana, and the meaning ethics.